Teologi Mustad’afin di Indonesia: Kajian atas Teologi Muhammadiyah - Sokhi Huda (Universitas Darussalam Gontor, 2011)
Mustad’afin Theology in Indonesia is the new face of al-Ma’un theology initiated by the Ahmad Dahlan. It eventually accumulates with more extensive issues and involves partnerships with other parties in order to achieve its praxis strategy. The basic assumption of this theology is that the practice of worship must be directly related to social concerns, with a foundation of monotheism that manifests itself into the realm of praxis. This finally leads to the key words of “social unity” and “social rituals” which are then developed in the context of contemporary nationhood and statehood in Indonesia. Moreover, its epistemology primarily comes from: (1) Wahhabi-Salafi ideology of Rashid Rida, (2) the idea of education reform of Muhammad ‘Abduh, and (3) theology of al-Ma’un of Ahmad Dahlan. These three basic epistemologies are equipped with a significant adaptation to seven factors, in order to be accepted as a theology of liberators movement in Indonesia. The performance of Mustad’afin theology is a theology that does social defense for the following conditions: (1) oppression of faith, (2) retardation, (3) suffering of economic and social status, (4) moral suffering, and (5) the threat of theologies and the existence of Indonesia. Finally, it implies the necessity of Mustad’afin Islamic Jurisprudence to regulate the conduct of worship and social community. Furthermore, the exclusive part of Wahhabi-Salafi Islamic jurisprudence is no longer posed.